Interest-Free Treasury Bonds (IFTB) - Bidabad, Bijan (International Journal of Shari’ah and Corporate Governance Research, 2019)
Purpose: Although the treasury bill is the most important monetary instrument in central banking, its application in different phases of the business cycle, especially in a liquidity trap, is not working well. To remove this obstacle “Interest-Free Treasury Bond” (IFTB) is introduced as a substitute for conventional treasury bills. Design: IFTB is a valuable paper which is issued by government treasury through a barter contract and is sold to central or commercial banks. The issuer is a debtor to the holder and has to pay back the nominal value at maturity; in addition, the issuer is committed to lending a similar amount of money to the paper holder for an equal period. Zero interest rate is nominated for lending and borrowing. Finding: IFTB is a zero-coupon, asset-backed note with no interest and is designed upon “debt equal to future loan”, or “loan equal to future debt” with “time-withdrawal right”. The paper holder can supply and transact her bond in the secondary market at a competitive price. Practical implication: It can be used as a substitute for conventional treasury bills. All conventional and non-usury systems can implement IFTB. JEL: E43, E44, E52, E58, E62, E63